Pure & simple : homemade Indian vegetarian cuisine - Mittal, Vidhu (Northhampton, Mass. : Interlink, 2009)
A mouthwatering collection of recipes reflecting the very best of Indian vegetarian cuisine presents more than 100 classic and contemporary recipes that are easy to prepare. Included is information on spices, vegetables, and kitchen tools, along with useful tips for each recipe.
Introduction -- Discover spices -- Know your vegetables -- Goodness of legumes -- Kitchen equipment -- Drinks, soups & salads -- Snacks & appetizers -- Main courses -- Rice & breads -- Accompaniments -- Desserts -- Cooking processes -- Meal menus -- Snack menus -- Glossary of food & cooking terms.
Keywords: Cooking, Indic; Vegetarian cooking; Cooking, Indic; Vegetarian cooking; Indic cooking; Vegetarian cooking; Nonfiction